One day to Fall - Beharrie, Therese ([Place of publication not identified] : [Carina Press], 2019)
Of all the taxis in all of Cape Town, Sophia Roux had to stumble into his. She should be at her "perfect" sisters bedside, awaiting the arrival of the newest member of her family. But the thought of spending hours at the hospital with her suffocating relatives has Sophia hailing the first taxi she sees. Only to realise too late that the man at the wheel of her getaway car is the most unpleasant one shes ever had the misfortune to meet. Parker Jones, the handsome yet surly driver in question, is used to dealing with baggage of the family variety. And it just so happens hes in need of temporary escape from his own. Witty banter with a beautiful--if exasperating--woman while chauffeuring her around the city on a gorgeous spring day makes for an ideal break from reality. But a lot can happen in twenty-four hours: babies can be born, family can reconnect. And maybe the most unlikely pair can fall in love. One-click with confidence. This title is part of the Carina Press Romance Promise: all the romance youre looking for with an HEA/HFN. Its a promise! This book is approximately 72,000 words
Keywords: Taxicab drivers -- Fiction; Families -- Fiction; Man-woman relationships -- Fiction; Romance fiction; Downloadable electronic books; Electronic books